Pengaruh Gadget Terhadap Perkembangan Kognitif Anak Usia Dini - indra bangsawan; Ridwan Ridwan; Naelul Fauziyah (Jurnal PG-PAUD, 2022)
The Effect of Gadgets on Early Childhood Cognitive Development. The purpose of the study was to determine the effect of using gadgets on the cognitive development of early childhood in Teluk Pulai Raya Village, Tanjung Jabung Barat Regency. This study uses quantitative research methods, with a One-Shot Case Study research design. The data collection techniques in this study were observation and questionnaires, the population in this study was children aged 5-6 years in RT 5. Data collection techniques used parametric analysis. Based on the calculation results, the average value is 25 and the standard deviation is 40.22. Then from these results, a hypothesis test (t test) was carried out using a parametric one sample test. Based on the results of the analysis carried out, the results obtained t = 3.76. This value is greater than the value of t_table with a significant level of 5% or  = 3.76  = 2.20. This means that there is a significant effect of using gadgets on the cognitive development of early childhood in Teluk Pulai Raya Village, Tanjung Jabung Barat RegencyTujuan penelitian adalah untuk mengetahui pengaruh penggunaan gadget terhadap perkembangan kognitif anak usia dini di Desa Teluk Pulai Raya Kabupaten Tanjung Jabung Barat. Penelitian ini menggunakan metode penelitian kuantitatif, dengan desain penelitian One-Shot Case Study. Teknik pengumpulan data dalam penelitian ini yaitu observasi dan kuesioner, populasi dalam penelitian ini sebanyak 12 orang anak usia 5-6 tahun. Jumlah sampel yang digunakan sebanyak 12 orang anak. Teknik pengumpulan data menggunakan analisis parametrik. Berdasarkan hasil perhitungan didapat nilai rata-rata 25 dan standar deviasinya 40,22. Kemudian dari hasil tersebut dilakukan uji hipotesis (uji t) menggunakan uji satu sampel parametrik. Berdasarkan hasil analisis yang dilakukan diperoleh hasil t = 3,76 . Nilai ini lebih besar dari nilai   dengan taraf signifikan 5% atau  = 3,76   = 2,20.  Artinya terdapat pengaruh positif yang signifikan penggunaan gadget terhadap perkembangan kognitif anak usia dini di Desa Teluk Pulai Raya Kabupaten Tanjung Jabung Barat Keywords: Gadget, Perkembangan Kognitif, anak usia diniDOI: http://dx.doi.org/10.23960/jpa.v8n1.24067